Lived Experiences and Life Satisfaction of ChildFree Women in Late Life. (April 2020) - Stahnke, Brittany; Blackstone, Amy; Howard, Heather
The purpose of this study was to gain a deeper understanding of the overall life satisfaction of older adult women who have not had children. We explore the following questions: (1) What is the overall sense of life satisfaction of childfree women over 65 years of age? (2) What is the lived experience of being a childfree woman in U.S. society? and (3) How does being childfree inform women's overall life satisfaction? Using a phenomenological research design to analyze data from interviews with 14 childfree women over the age of 65, we found that nearly all participants report a high life satisfaction and many report a strong sense of resiliency, though they also report an awareness of the stigma associated with their status as nonmothers. Implications for both theory and practice are considered.